A model of labeling with horizontal differentiation and cost variability - Saak, Alexander E. (Wiley, 2011)
We study optimal disclosure of variety by a multiproduct firm with random costs. The prices for labeled varieties are increasing functions of the cost differential and do not reveal which variety is cheaper to produce. Nondisclosure is most common under moderate uncertainty about costs and not too much idiosyncrasy in valuations and quality asymmetry. Mandatory disclosure decreases expected welfare when cost variability is large and quality asymmetry is small. The cheaper variety tends to be oversupplied (undersupplied) when disclosure is voluntary (mandatory). Competition among multiproduct firms that source inputs in the same upstream market may not lead to more disclosure.